Review of Current Principles of the Diagnosis and Management of Brain Metastases - Brenner, Alex W.; Patel, Akash J. (Frontiers in Oncology, 2022)
Brain metastases are the most common intracranial tumors and are increasing in incidence as overall cancer survival improves. Diagnosis of brain metastases involves both clinical examination and magnetic resonance imaging. Treatment may involve a combination of surgery, radiotherapy, and systemic medical therapy depending on the patient’s neurologic status, performance status, and overall oncologic burden. Advances in these domains have substantially impacted the management of brain metastases and improved performance status and survival for some patients. Indications for surgery have expanded with improved patient selection, imaging, and intraoperative monitoring. Robust evidence supports the use of whole brain radiotherapy and stereotactic radiosurgery, for both standalone and adjuvant indications, in almost all patients. Lastly, while systemic medical therapy has historically provided little benefit, modern immunotherapeutic agents have demonstrated promise. Current investigation seeks to determine the utility of neoadjuvant radiotherapy and laser interstitial thermal therapy, which have shown benefit in limited studies to date. This article provides a review of the epidemiology, pathology, diagnosis, and treatment of brain metastases and the corresponding supporting evidence.